Kredibilitas Media Online Dalam Pemberitaan Rencana Aktivitas Pembelajaran Secara Tatap Muka Pada Tahun 2021 Dimasa Pandemi Covid - 19 - Siti Qona’ah -; Gan Gan Giantika; Ichsan Widi Ichsan Widi Utomo; Fitriyanto - - (Jurnal Komunikasi, 2021)
Abstract  -The purpose of this study was to determine the credibility of Okezone's online media in reporting face-to-face learning activity plans in 2021 during the Covid-19 pandemic which included three dimensions, namely trust, presentness, and unbiasedness. The method used in this research is descriptive qualitative method, using the method of interviewing, literature study and observation. Methodology with a qualitative approach is used in order to have a complete and in-depth picture of the problem under study. The results of this study concluded that the credibility of online media in reporting face-to-face learning activity plans in 2021 during the Covid -19 pandemic was positive. Broadly speaking, the credibility of Okezone online media in reporting face-to-face learning activity plans in 2021 is a credible online media. However, there are a number of things that need to be considered again in terms of the completeness of the news presented, but this does not affect student opinions regarding trust, currentness and bias towards news in Okezone Online Media regarding reporting of face-to-face learning activity plans in 2021. Keywords: credibility, online media, Covid-19 pandemic